2020
DOI: 10.3390/vaccines8030468
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Nutraceuticals and Immune System Modulation: An Evidence-Based Overview

Abstract: Immunomodulators are agents able to affect the immune system, by boosting the immune defences to improve the body reaction against infectious or exogenous injuries, or suppressing the abnormal immune response occurring in immune disorders. Moreover, immunoadjuvants can support immune system acting on nonimmune targets, thus improving the immune response. The modulation of inflammatory pathways and microbiome can also contribute to control the immune function. Some plant-based nutraceuticals have been studied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 220 publications
1
31
0
Order By: Relevance
“…It is well-established that moderate physical activity enhances immune functions [ 32 , 33 , 34 ], but intense exercise induces inflammation, alters phagocytic and cytotoxic functions, decreases mucosal IgA, and increases the susceptibility to infections, especially URTI [ 40 , 42 ]. In recent years, flavonoids have shown immunomodulatory properties in both animal and human studies [ 139 , 140 , 141 , 142 ]. In fact, a recent review [ 142 ] demonstrated that flavonoid consumption decreases the URTI incidence by 33% compared to the control, and two studies [ 143 , 144 ] found significant reductions in URTI symptoms with cranberry beverages or garlic extract.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that moderate physical activity enhances immune functions [ 32 , 33 , 34 ], but intense exercise induces inflammation, alters phagocytic and cytotoxic functions, decreases mucosal IgA, and increases the susceptibility to infections, especially URTI [ 40 , 42 ]. In recent years, flavonoids have shown immunomodulatory properties in both animal and human studies [ 139 , 140 , 141 , 142 ]. In fact, a recent review [ 142 ] demonstrated that flavonoid consumption decreases the URTI incidence by 33% compared to the control, and two studies [ 143 , 144 ] found significant reductions in URTI symptoms with cranberry beverages or garlic extract.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the authors identified type II arabinogalactan proteins, members of a large and diverse family of cell surface-expressed proteoglycans present in plant cell walls [ 39 ], as the immunostimulatory moiety in kanuka honey [ 38 ]. This is an interesting observation since these proteins have been demonstrated to possess immunostimulatory properties in a limited number of studies [ 40 , 41 ]. However, the precise mechanism by which these glycoproteins affect immune cell function remains unknown.…”
Section: Immunomodulatory Properties Of Honey: Induction Of Proinflammatory Cytokines By Myeloid Cellsmentioning
confidence: 99%
“…They often manifest numerous activities, sometimes pleiotropic, and can be further used with encouraging results as nutraceuticals (in prevention) and therapeutic strategies as well. Immunomodulators are a good example of plant-based nutraceuticals, being endowed with good potential as immune system stimulants, counteracting infectious and/or exogenous lesions, with immunosuppressive effect in controlling abnormal immune responses due to autoimmune diseases or/and as adjuvants contributing to modulation of nonimmune targets [ 154 ].…”
Section: Herbs Considered Usable For the Treatment Of Covid-19mentioning
confidence: 99%